2023
DOI: 10.3389/fpls.2023.1143863
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic assessment of drought stress vulnerability in grasslands of Xinjiang, China

Abstract: In the process of climate warming, drought has increased the vulnerability of ecosystems. Due to the extreme sensitivity of grasslands to drought, grassland drought stress vulnerability assessment has become a current issue to be addressed. First, correlation analysis was used to determine the characteristics of the normalized precipitation evapotranspiration index (SPEI) response of the grassland normalized difference vegetation index (NDVI) to multiscale drought stress (SPEI-1 ~ SPEI-24) in the study area. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 109 publications
0
9
0
Order By: Relevance
“…Prior modeling studies have indicated that indirect effects are more significant in arid regions than in humid areas [68,69]. In our study, SEM revealed that topographic variations and the consequent changes in water-heat conditions were identified as the primary factors affecting vegetation growth in the Xinjiang region [70,71]. Therefore, the discrepancy in moisture input caused by the mountains may result in notable differences in the arid climate of the northern and southern Tianshan Mountains, especially in terms of temperature, precipitation, and soil, thereby establishing a natural ecosystem in the plains consisting of alpine meadows, mid-mountain humid forests, semiarid grasslands, and arid deserts [72].…”
Section: Analysis Of Driving Factors Of the Fvc Spatial Patternmentioning
confidence: 53%
“…Prior modeling studies have indicated that indirect effects are more significant in arid regions than in humid areas [68,69]. In our study, SEM revealed that topographic variations and the consequent changes in water-heat conditions were identified as the primary factors affecting vegetation growth in the Xinjiang region [70,71]. Therefore, the discrepancy in moisture input caused by the mountains may result in notable differences in the arid climate of the northern and southern Tianshan Mountains, especially in terms of temperature, precipitation, and soil, thereby establishing a natural ecosystem in the plains consisting of alpine meadows, mid-mountain humid forests, semiarid grasslands, and arid deserts [72].…”
Section: Analysis Of Driving Factors Of the Fvc Spatial Patternmentioning
confidence: 53%
“…In Xinjiang, the northern part is dominated by the Altai Mountains, the southern part is characterized by the Kunlun Mountain range, and the central part is the Tianshan Mountains. These mountain ranges divide Xinjiang into the Tarim Basin in the south and the Junggar Basin in the north ( Han et al., 2023 ). The geographical environment in Xinjiang gives rise to a typical temperate continental climate, where maritime air masses have limited reach.…”
Section: Methodsmentioning
confidence: 99%
“…Different grassland types have different physiological characteristics and different response characteristics to drought. Han et al (2023) explored the differences in the probability of drought stress in Xinjiang from different grassland types, but the hysteresis characteristics of different grassland types to drought need to be further explored. Soil moisture is a primary limiting factor for vegetation growth in arid and semiarid regions.…”
Section: Lagged Effect Of Drought On Grassland Nppmentioning
confidence: 99%
“…More meteorological data should be integrated for analysis in the future. Meanwhile, to explore the response characteristics of different grassland types NPP to drought, this study used the GLC2000 dataset to classify grassland types, which has a high spatial resolution and detailed classification and is widely used in grassland studies (Wang et al, 2016;Liu et al, 2019;Han et al, 2023). However, as land use/cover is dynamic and its changes may have some impact on grassland NPP and drought (Shen et al, 2020;Ma et al, 2022), future studies can integrate multiple land cover datasets to reflect grassland distribution more accurately.…”
Section: Uncertainty and Future Researchmentioning
confidence: 99%